Effect of Baoshenfang Formula on Podocyte Injury via Inhibiting the NOX-4/ROS/p38 Pathway in Diabetic Nephropathy - Fang-qiang Cui; Long Tang; Yan-bin Gao; Yue-fen Wang; Yuan Meng; Cun Shen; Zi-long Shen; Zhi-qiang Liu; Wen-jing Zhao; Wei Jing Liu (Journal of Diabetes Research)
Diabetic nephropathy (DN) is a serious kidney-related complication of type 1 and type 2 diabetes. The Chinese herbal formula Baoshenfang (BSF) shows therapeutic potential in attenuating oxidative stress and apoptosis in podocytes in DN. This study evaluated the effects of BSF on podocyte injury in vivo and in vitro and explored the possible involvement of the nicotinamide adenine dinucleotide phosphate-oxidase-4/reactive oxygen species- (NOX-4/ROS-) activated p38 pathway. In the identified compounds by mass spectrometry, some active constituents of BSF were reported to show antioxidative activity. In addition, we found that BSF significantly decreased 24-hour urinary protein, serum creatinine, and blood urea nitrogen in DN patients. BSF treatment increased the nephrin expression, alleviated oxidative cellular damage, and inhibited Bcl-2 family-associated podocyte apoptosis in high-glucose cultured podocytes and/or in diabetic rats. More importantly, BSF also decreased phospho-p38, while high glucose-mediated apoptosis was blocked by p38 mitogen-activated protein kinase inhibitor in cultured podocytes, indicating that the antiapoptotic effect of BSF is p38 pathway-dependent. High glucose-induced upexpression of NOX-4 was normalized by BSF, and NOX-4 siRNAs inhibited the phosphorylation of p38, suggesting that the activated p38 pathway is at least partially mediated by NOX-4. In conclusion, BSF can decrease proteinuria and protect podocytes from injury in DN, in part through inhibiting the NOX-4/ROS/p38 pathway.